(untitled) (Vietnam Journal of Community Medicine, 2022)
The study was carried out on 119 children aged 6-23 months. Objectives: To evaluate the improvement of biochemical and hematological indices of 6-23 months old children supplemented with bibomix multi-micronutrient powder after treatment for acute respiratory infections. Methods: Controlled intervention. RESULTS: The biochemical-hematological indexes have improved markedly: Serum iron of the intervention group has increased by 6.6 ± 4.2 μmol/L while in the control group it has only increased by 1.6 ± 2.4 μmol/L (higher than 4.10 μmol/L), (p=0.0000). Transferrin of the intervention group decreased (-147.2 ± 321.6 mg/dL) more than the control group (21.9 ± 520.3 mg/dL) (reduced -169.08 mg/dL; p= 0.0170). Serum zinc content of the intervention group increased by 1.90 ± 3.17 µmol/L (increased 0.97 µmol/L) compared to the control group (0.03 ± 3.26 µmol/L); statistically significant difference p=0.0001. The hemoglobin content of both groups tended to decrease, but in the intervention group, the decrease was less.